What's the catch in who fishes? Fisherwomen's contributions to fisheries and food security in Marovo Lagoon, Solomon Islands. (October 2019) - Rabbitt, Sheridan; Lilley, Ian; Albert, Simon; Tibbetts, Ian R.
Abstract: Food security is arguably one of the greatest challenges facing humanity. With rapid globalisation, and the global population forecast to reach 9.7 billion by 2050, this problem will only intensify. Fresh fish is the primary source of animal protein for many nations, and this is particularly true for equatorial nations in the Pacific. As fish stocks strain under climate change and increasing fishing pressure, their decline and collapse is becoming a common story. Predicted changes in fish populations indicate that equatorial nations will likely bear the brunt of nutritional insecurity, and this is particularly likely for Pacific nations where agricultural land is limited [1]. Given global threats to fisheries, and their importance to village diets in the Pacific, it is critical that fisheries resources are well managed to ensure food security for future generations. We interviewed 87 women across three villages in Marovo Lagoon, Western Province, Solomon Islands about their role in fisheries and fishery-related activities within their communities. Of the women interviewed, 80.7% indicated that they do fish or harvest invertebrates. 84.5% of fisherwomen were primarily targeting finfish, not invertebrates, and most women (59.4%) indicated that they harvested seafood solely to feed their families. Results from this study contribute to a growing body of literature highlighting the high involvement of women in small-scale fisheries, and their contributions to household food security. This knowledge broadens our understanding of fishery resource utilization in the Solomon Islands, and provides data for strengthening food security through improved fisheries management. Highlights: Nutritional security in Solomon Islands relies strongly on sustainable fisheries. Fisheries managers require a complete picture of fisheries harvest, but data on women's roles and harvest is still lacking. Women involved in this study were involved in different aspects of fishery harvest, but dominated in nearshore environments. Most respondents were found to target finfish over invertebrates, and fished primarily to feed their families. Understanding how women engage with fisheries is important for maintaining nutritional security in Solomon Islands.